2016
DOI: 10.1002/jmri.25558
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of recurrent high‐grade gliomas treated with bevacizumab: A preliminary report of 3D pseudocontinuous artery spin labeling

Abstract: 3 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2017;46:565-573.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Relevant articles were selected according to PRISMA (see relevant flow chart in Figure 1). 104 of them were excluded as they did not met the research question; for example: they applied ASL in animal models [13] use ASL in order to asses the treatment [14, 15] or applied in pediatric population [16]. Eventually, 18 studies were deemed eligible in terms of the selected inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Relevant articles were selected according to PRISMA (see relevant flow chart in Figure 1). 104 of them were excluded as they did not met the research question; for example: they applied ASL in animal models [13] use ASL in order to asses the treatment [14, 15] or applied in pediatric population [16]. Eventually, 18 studies were deemed eligible in terms of the selected inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have assessed the detection of residual tumor shortly after surgery. 84 ASL has shown success at predicting and monitoring response to bevacizumab, 85 , 86 an anti-angiogenic agent. ASL has also shown value in differentiating pseudoprogression from recurrence.…”
Section: Practical Acquisition and Post-processingmentioning
confidence: 99%
“…The authors measured CBF before and after treatment in 16 patients with recurrent high-grade glioma receiving bevacizumab-combined chemotherapy and determined that both rCBF with the cerebellar CBF as the reference before treatment and the average magnitude of the change in CBV (aCBF) before and after treatment were significantly associated with OS and PFS. The study suggested that the FSE pcASL technique might be useful for generating predictive images ( Lyu et al, 2017 ).…”
Section: Physiological Parameters In Anti-angiogenic Therapymentioning
confidence: 99%